Learning continuous integration with teamcity : master the principles and practices behind continuous integration by setting it up for different technology stacks using teamcity /: master the principles and practices behind continuous integration by setting it up for different technology stacks using teamcity. (2014) - Mahalingam, Manoj S
No abstract available